A reply to Keyan Tomaselli’s "The 2022 Copyright Amendment Bill: Implications for the South African universities’ research economy" - Klaus D Beiter (Communicare)
Rather than focusing on the intricate detail of the Copyright Amendment Bill (CAB), the purpose of this short reply is to outline the broader context against which copyright reform, as it affects the higher education and scientific spheres, must be understood. This context demonstrates that provisions such as Section 12A (fair use, inter alia for purposes of research and education) or Section 12D (allowing substantial reproduction, sometimes of whole textbooks, for educational purposes) constitute a bare minimum of “what is required,” and also permissible under international copyright law.